2019
DOI: 10.1093/ejcts/ezz149
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal aortic flow profiles persist after aortic valve replacement in the majority of patients with aortic valve disease: how model-based personalized therapy planning could improve results. A pilot study approach

Abstract: OBJECTIVES Complex blood flow profiles in the aorta are known to contribute to vessel dilatation. We studied flow profiles in the aorta in patients with aortic valve disease before and after surgical aortic valve replacement (AVR). METHODS Thirty-four patients with aortic valve disease underwent 4-dimensional velocity-encoded magnetic resonance imaging before and after AVR (biological valve = 27, mechanical valve = 7). Seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Furthermore, the same model was used for simulation of hemodynamics in patients suffering from aortic coarctation, another stenotic disease that affects the aorta. Here, simulated flow fields correlated well with velocity fields measured by 4D velocity encoded MRI [25] and accurately calculated the pressure drop across the stenosis [12]. The accuracy of the pressure drop calculation was validated against catheter-measured pressure drops.…”
Section: Limitationsmentioning
confidence: 62%
“…Furthermore, the same model was used for simulation of hemodynamics in patients suffering from aortic coarctation, another stenotic disease that affects the aorta. Here, simulated flow fields correlated well with velocity fields measured by 4D velocity encoded MRI [25] and accurately calculated the pressure drop across the stenosis [12]. The accuracy of the pressure drop calculation was validated against catheter-measured pressure drops.…”
Section: Limitationsmentioning
confidence: 62%
“…The applicability of radiomics analysis to characterize flow profiles is tested with data from two additional independent studies. A dataset of patients with aortic stenosis ( 22 ) represents a cohort of pathological cases, while a dataset from a population study in the city of Freiburg, Germany ( 23 ) serves as control. We were able to include six additional cases in the latter dataset, which could not be analyzed in the initial study.…”
Section: Methodsmentioning
confidence: 99%
“…Abnormal blood flow profiles in the thoracic aorta, as well as resulting changes in hemodynamic parameters such as wall shear stresses, are present in aortic valve and wall diseases and have been shown to be associated with progression in aortic dilation (Nordmeyer et al 2020) aortic aneurysm formation (Hope et al 2007) and aortic dissection (Ben Ahmed et al 2016. For the quantitative assessment of eccentric systolic flow in the aorta, for example, the parameter normalized flow displacement (NFD) has been introduced (Sigovan et al 2011(Sigovan et al , 2015, and NFD values above 0.2 have shown to be associated with up to four times higher aortic growth rate (Burris et al 2014), however, age-and sex-specific normative ranges have not yet been published.…”
Section: Introductionmentioning
confidence: 99%
“…Many other blood flow properties are still described qualitatively by subjective grading using ordinal levels, such as 'none', 'mild' and 'marked' (Bürk et al 2012, van Ooij et al 2017, Guala et al 2019, Nordmeyer et al 2020. More recent studies suggested a volume-based assessment of these properties and related the information to vessel segments instead of cross-sections (Garcia et al 2017, van Ooij et al 2021.…”
Section: Introductionmentioning
confidence: 99%